ABOUT THE MODIFICATION OF FISCAL RULES IN OF INVESTMENT DEVELOPMENT OF THE RUSSIAN ECONOMY - V. V. Maslennikov; M. R. Pinskaya (Финансы: теория и практика)
The article analyzes the problem of modifying the budget rules while facing a slowdown of the economic growth in Russia in the context of high levels of natural rent. It was revealed that the main disadvantage of the current fiscal rules is the lack of coordination with the investment and monetary policy. Modifying the existing budget rules is proven to be necessary for the transfer of the natural rent in the infrastructure development and the diversification of the economy.The basis of the new fiscal rules is the mechanism for maintaining a balance between cash flows in consumption funds, investment, and savings. This requires formation of an Investment fund for the development of the national economy, filled not only by the state rental revenues, but the Bank of Russia as well (especially in the period of low oil prices).